Agricultural economics and transition: What was expected, what we observed, the lessons learned. Proceedings (Volume I) - Csaba Csáki; Csaba Fogács (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2008)
Over fifteen years have elapsed since the process of transition from the socialist system started in the early 1990s. During this time, Central and Eastern Europe and Central Asia have undergone profound structural change with wide variation in the amount of transformation in rural areas. In retrospect, it can be seen that the countries that chose to transform their socialized agriculture into a private-ownership and market-based system experienced the most positive economic performance. These countries in 2004 became members of the European Union, and left the classical stages of transition behind. Looking at the developments of the past one and a half decade, it is clear, however, that the initial expectations for the transformation in the bulk of the region were overly optimistic and the transition process in agriculture is far more complex than originally envisaged. It is widely recognized, for instance, that the importance of functioning institutions was underestimated at the outset of the transition. Increased social problems and alarming signs of increasing poverty and inequality have also added a new, unexpected, dimension to the transition process. This Seminar provided an excellent opportunity to discuss the process and the status of transition in agriculture as well as to review of the status of agricultural economics profession in the region. CONTENTS: Foreword; Csaba Csáki, Csaba Forgács. A Joint IAAE-EAAE Seminar summary comments; Csaba Csáki. The profession of (agricultural) economists and the experience of transition; Ulrich Koester. Measuring the success of agricultural transition: An application to Russia; William M. Liefert. Competitiveness in the food industry: A CGE modeling approach to assess foreign direct investment in transition countries; Martin Banse, S. H. Gay, S. Mcdonald, R. M'barek, Johan F. M. Swinnen. Policy reform and agricultural productivity in transition countries; Hanho Kim, Donghwan An. Changes in the structure of agricultural production, farm structure and income in Hungary in the period of 2004-2006; Gábor Szabó. Shaping agribusiness and its impact on the competitive environment of agricultural enterprises; Vera Becvárová. Transition and foreign trade: The case of the Ukrainian agri-food sector; Inna Levkovych, Heinrich Hockmann. The development of the hungarian agricultural trade after the EU accession; Gábor Konig. Agricultural transition and integration to the world economy: NIS case; Eugenia Serova. Diversification of rural incomes and non-farm rural employment: Evidence from Russia; Dmitry Zvyagintsev, Olga Shick, Eugenia Serova, Zvi Lerman. Accounting for heterogeneity bias in efficiency models: An application to Polish agriculture; Heinrich Hockmann, Agata Pieniadz. Transformational crisis, transformational depression in the agriculture. The Hungarian case; Péter Halmai, Viktória Vásáry. The main bottlenecks of the rural knowledge transfer in Romania; Mária Vincze, Andrea Kölcsey. Studying investment patterns in Russian agriculture; Raushan Bokusheva, Irina Bezlepkina, Alexander Kupavyc. Changes in the Romanian farm structures during transition - Evolution and main determinants; Crina Turtoi, Camelia Toma, Camelia Gavrilescu. A time-series analysis of the beef livestock supply in Russia: Implications for agricultural sector development policies; Maria Antonova, Manfred Zeller. Agricultural recovery in CIS: Lessons of 15 years of land reform and farm restructurin; Zvi Lerman. Land market development and agricultural production efficiency in Albania; Klaus Deininger, Sara Savastano, Gero Carletto, The persistence of the corporate farms: They survived the transition but do they have future under the CAP; Laure Latruffe, Sophia Davidova, Gejza Blaas. Land use and land reform in some former Central and East European countries; Katalin Takács-György, Anna Bandlerova, Adam Sadowski. Romania: Semi-subsistence farm sector, result of wrong strategic approach? Lucian Luca. Farm-level determinants of conversion to sustainable farming practices in the New Members States; Adriana Cristoiu, Francisco Cáceres-Clavero, Blanca Lucena-Cobos. The economics of farm organization in CEEC and FSU; Pavel Ciaian, Jan Pokrivcak, Dusan Drabik. The structure of individual (family) farms in Hungary; Anna Burger, Katalin Szép. Facing the future: Strategies and investment behaviour of Polish farmers; S. Gomez y Paloma, E. Majewski, M. Raggi, D. Viaggi
urn:nbn:de:gbv:3:2-18853
Keywords: 330